Combination of etodolac and dexamethasone improves preemptive analgesia in third molar surgery: a randomized study - Ramires, Guilherme André D. [UNESP]; de Souza Santos, Anderson Maikon [UNESP]; Momesso, Gustavo A. C. [UNESP]; Polo, Tárik Ocon B. [UNESP]; Silva, William P. P. [UNESP]; Barbosa, Stéfany [UNESP]; Bassi, Ana Paula F. [UNESP]; Faverani, Leonardo Perez [UNESP] (Springer Nature, 2020)
Objective: This randomized, controlled, triple-blind, crossover clinical trial aimed to investigate the use of dexamethasone (DEX) and etodolac (ETO) as preemptive analgesia before mandibular third molar extraction. Methods: Patients were divided into three groups (n = 20 teeth each) based on the drug administered: DEX 8 mg (DEX); DEX 8 mg plus ETO 300 mg (DEX + ETO), and ETO 300 mg (ETO). Paracetamol (750 mg) tablets were administered as rescue analgesics. Pain was evaluated using the visual analog scale (VAS) at 6, 12, 24, 48, and 72 h and 7 days postoperatively. Edema and trismus were assessed 48 and 72 h postoperatively. All data were subjected to statistical analysis, where a P value <.05 indicated statistical significance. Results: VAS scores and the number of rescue analgesics taken were lower in the DEX + ETO group than in the other groups (P <.001 and P =.014, respectively). At 48 h, trismus was similar among all groups; however, the ETO group showed the highest trismus 7 days postoperatively (P <.05). Edema was similar among all groups at all time points (P >.05). Conclusion: The combined use of the anti-inflammatory drugs, DEX and ETO, resulted in better pain control and the need for fewer rescue analgesics than the use of either drug alone, which indicated their effectiveness in mandibular third molar extractions preoperatively. Clinical relevance: This drug combination can lead to less pain, edema, and trismus and reduce the use of rescue analgesics in the postoperative period.
Keywords: Analgesia; Anti-inflammatory agents; Edema; Third molar